2005
DOI: 10.1093/jn/135.9.2103
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucine, a Blood Glucose-Lowering Amino Acid, Increases Glucose Uptake in Rat Skeletal Muscle in the Absence of Increases in AMP-Activated Protein Kinase Activity

Abstract: Leucine and isoleucine were shown to stimulate insulin-independent glucose uptake in skeletal muscle cells in vitro. In this study, we examined the effects of leucine and isoleucine on blood glucose in food-deprived rats and on glucose metabolism in skeletal muscle in vivo. Furthermore, we investigated the possible involvement of the energy sensor, 5'-AMP-activated protein kinase (AMPK), in the modulation of glucose uptake in skeletal muscle, which is independent of insulin, and also in leucine- or isoleucine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 27 publications
11
93
0
2
Order By: Relevance
“…Valine was excluded from the scope of this research, as valine caused an increase in plasma glucose levels. Oral administration of isoleucine, but not leucine, significantly decreased plasma glucose concentration in food-deprived rats (9). Glucose uptake in the skeletal muscle did not differ after leucine administration, but glucose uptake in the muscles of rats administered isoleucine was 73% greater than that in food-deprived controls, thus suggesting that isoleucine increases skeletal muscle glucose uptake in vivo.…”
Section: Hypoglycemic Effect Of Isoleucinementioning
confidence: 76%
See 1 more Smart Citation
“…Valine was excluded from the scope of this research, as valine caused an increase in plasma glucose levels. Oral administration of isoleucine, but not leucine, significantly decreased plasma glucose concentration in food-deprived rats (9). Glucose uptake in the skeletal muscle did not differ after leucine administration, but glucose uptake in the muscles of rats administered isoleucine was 73% greater than that in food-deprived controls, thus suggesting that isoleucine increases skeletal muscle glucose uptake in vivo.…”
Section: Hypoglycemic Effect Of Isoleucinementioning
confidence: 76%
“…However, the pharmacological effects of the other BCAAs, isoleucine and valine, have not been well clarified. We recently found that among the BCAAs, isoleucine acts as a nutrient regulator of glucose metabolism (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, it plays a slightly different role; in particular it is a factor in carbohydrate metabolism. It stimulates the capture and, independently from insulin and mTOR, transport of glucose in skeletal muscles (5). In contrast to leucine, it does not exhibit anabolic properties by increasing protein synthesis in skeletal muscles: it does not increase the activation of translation initiation factors (7).…”
Section: Discussionmentioning
confidence: 99%
“…Resultados similares foram encontrados por Doi et al (2005), quando administraram via oral uma concentração de 1,35 g de L-leucina/kg de peso em ratos, sem encontrar diferença na concentração de insulina plasmática no músculo gastrocnêmio uma hora após a administração.…”
Section: Aminoácidos De Cadeia Ramificada E Regulação Da Síntese Protunclassified